Productivity of a collection of butternut squash in villa Mercedes, province of san Luis, using two planting systems - Luna, Sergio Alejandro (2019)
Argentina faces challenges in optimising population diet for quantity and diversity of horticultural products, given that consumption is only a third of that recommended by the WHO and tending to decrease, and that only four species represent 70% of total consumption. With the objective of promoting the expansion of a promising crop, butternut squash, a completely randomised trial was initiated in San Luis, Argentina (33°39?29? S 65°28?82? W) between 8/12/2015 and 11/04/2016, aimed at evaluating the productivity (yield in kg.ha-1, plus units.ha-1) under two planting systems (transplanted pot-grown seedlings (MT) and direct drilling (SD)) at a plant density of 0.8 x 2.5 m, of the following collection of innovative cultivars from INTA-La Consulta: Dorado INTA-MAPO, Paquito-INTA, Cuyano-INTA, Frontera-INTA and Cokena-INTA, with the following results. MT gave 35% more units.ha-1 than SD (MT: 25524a and SD: 18905b) and 43.4% more yield (MT: 25476ª and SD: 17762b). The highest yielding genotypes were Frontera-INTA: 33013a, Cokena-INTA: 28957ab and Dorado-INTA-MAPO: 24015bc, whereas those producing the highest units.ha-1 were Frontera-INTA 26190a, Dorado-INTA-MAPO: 24047ab and Cuyano-INTA: 21905abc, followed by Cokena-INTA: 20119bc and Paquito-INTA: 18809c. Under MT, the highest yielding genotypes were Cokena-INTA: 37024a, Frontera-INTA: 36934a and Dorado-INTA-MAPO: 27348ª kg.ha-1, and the highest units.ha-1 were given by Frontera-INTA 29524ª, Dorado-INTA-MAPO: 26905ª and Cokena-INTA: 25476ª. Two of these high performers were the best under SD: Frontera-INTA: 29093a and Dorado-INTA-MAPO: 26683b kg.ha-1 and Frontera-INTA: 22857ª and Dorado-INTA: 21191a units.ha-1. In conclusion, the yield of Frontera-INTA and Cokena-INTA in San Luis was encouraging, especially under MT.